OPTIMALISASI PERAN STRATEGIS MANAJEMEN HUMAS DALAM MENINGKATKAN RESPONSIVITAS LAYANAN PUBLIK SEKOLAH DASAR: STUDI KUANTITATIF DI KOTA KARAWANG - Wahidin; Achmad Taufik Ismail; Chairil Fajar Hadiansyah; Fatimah Az Zahro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
As the vanguard of public education services, elementary schools play a vital role in responding to community demands. The responsiveness of public services is a crucial aspect in assessing school performance, and public relations management plays a strategic role in bridging communication between schools and the community. This study aims to analyze the influence of public relations management on the responsiveness of public services in elementary schools in Karawang Regency. This study uses a quantitative approach with a survey method of 93 respondents from a total population of 120, calculated using the Slovin formula with a margin of error of 5%. The research instrument is a questionnaire processed using SmartPLS. The results of the study indicate that public relations management has a significant effect on the responsiveness of public services. The implications of this study emphasize the importance of strengthening the public relations structure in elementary schools to improve the quality of education services.